Transformational leadership and innovation management: the mediating role of knowledge sharing - Wulansari, Puspita; Ganesha Pratama, Benedictus Kurnianda (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Indonesian universities are under increasing pressure to innovate in response to global competition, evolving educational demands, and the need for high-quality applied research. Transformational leadership plays a critical role in driving institutional adaptability, course delivery enhancement, and problem-solving capacity. However, limited empirical research has examined how transformational leadership fosters innovation management, particularly through the mediating role of knowledge sharing. This study investigates the effect of transformational leadership on innovation management, mediated by knowledge sharing, at XXX University in Bandung. Using a causal descriptive design with a quantitative approach, data were analyzed through Structural Equation Modeling (SEM) using Smart PLS 4.1. The study involved 100 lecturers selected through proportionate stratified random sampling. Findings reveal that transformational leadership significantly influences knowledge sharing (β = 0.6031, T = 5.7661, p < 0.0001) and directly affects innovation management (β = 0.614, T = 7.9821, p < 0.0001). Knowledge sharing also significantly contributes to innovation management (β = 0.364, T = 3.9125, p < 0.0001), and mediates the relationship between leadership and innovation (β = 0.2999, T = 3.7169, p = 0.0002). The study highlights the importance of leadership practices that promote knowledge exchange to strengthen institutional innovation. Future research should consider additional factors such as organizational culture and technological infrastructure.